THE IMPACT OF PHYSICAL ACTIVITY ON THE GUT MICROBIOME AND CLINICAL COURSE OF INFLAMMATORY BOWEL DISEASE - Katarzyna Adrianna Tryniecka; Diana Wisz; Filip Maciej Huzarski; Katarzyna Maria Turek; Weronika Worosz; Alicja Zań (International Journal of Innovative Technologies in Social Science, 2025)
Inflammatory bowel diseases (IBD), including ulcerative colitis and Crohn’s disease, are chronic disorders of complex and not yet fully understood etiology, involving genetic, immunological, and environmental factors. Increasing attention has been directed toward the role of the gut microbiome, whose disturbances play a significant role in the pathogenesis of these diseases. Concurrently, growing interest has been directed toward therapeutic strategies that support pharmacological treatment, including non-pharmacological interventions capable of modulating disease activity.Physical activity is recognized as one of the key determinants of overall health, and its role in inflammatory bowel diseases is of particular importance. Regular and moderate exercise promotes the maintenance of intestinal barrier function, exerts a beneficial effect on the composition and diversity of the gut microbiota, reduces inflammatory processes, and supports patients’ mental well-being. These effects may contribute to longer remission periods, improved treatment tolerance, and enhanced quality of life.Conversely, intensive and prolonged physical activity may act as a burden, potentially leading to destabilization of the intestinal barrier and exacerbation of disease symptoms. Therefore, proper adjustment of the type and intensity of physical activity represents an important component of supportive management.The aim of this paper is to present the current state of knowledge regarding the impact of physical activity on the gut microbiome, immune system function, and the clinical course of inflammatory bowel diseases, as well as to discuss its potential role in the prevention of extraintestinal complications and in the comprehensive improvement of patients’ quality of life.